Courtyard Sisters: Settler Fantasy and Experiment at the International Institute of Los Angeles, 1914–1940. Issue 4 (5th August 2021) - Dominguez, Laura
Abstract: This article examines the history of the International Institute of Los Angeles, one of dozens of immigrant-serving agencies to open nationwide under the Young Women's Christian Association (YWCA) during the 1910s. Close reading of this branch reveals how related processes of domestication, democratization, and assimilation of immigrant groups buttressed the settler colonial making of the city. Through a study of the organization's fieldwork, cultural programs, and architectural footprint, the author argues that the Institute preserved the racial fantasies of Anglo Angelenos with its efforts to Americanize women and girls in a Spanish Colonial Revival space. This article reframes the city's institutional landscape during the interwar period, showing how social reformers helped maintain and police boundaries of belonging in western metropoles.